High Titers of Low Affinity Antibodies in COVID-19 Patients Are Associated With Disease Severity - Hendriks, Jan; Schasfoort, Richard; Koerselman, Michelle; Dannenberg, Maureen; Cornet, Alexander Daniel; Beishuizen, Albertus; van der Palen, Job; Krabbe, Johannes; Mulder, Alide H. L.; Karperien, Marcel (Frontiers in Immunology, 2022)
Almost two years from the beginning of the COVID-19 pandemic there is still a lot unknown how the humoral response affects disease progression. In this study, we investigated humoral antibody responses against specific SARS-CoV2 proteins, their strength of binding and their relationship with COVID severity and clinical information. Furthermore, we studied the interactions of the specific Receptor Binding Domain in more depth by characterizing specific antibody response to a peptide library. We measured specific antibodies of isotypes IgM, IgG and IgA as well as their binding strength against the SARS-CoV2 antigens RBD, NCP, S1 and S1S2 in sera of 76 COVID-19 patients using Surface Plasmon Resonance imaging. Additionally, these samples were analyzed using a peptide epitope mapping assay, which consists of a library of peptides originating from the Receptor Binding Domain. A positive association was observed between disease severity and IgG antibody titers against all SARS-CoV2 proteins, and additionally for IgM and IgA antibodies directed against RBD. Interestingly, in contrast to the titer of antibodies, the binding strength went down with increasing disease severity. Within the critically ill patient group, a positive association with pulmonary embolism, d-dimer and antibody titers was observed. We hypothesize that in critically ill patients, antibody production and/or maturation may be ineffective. In the future, this approach may aid in predicting COVID-19 severity by measuring the quantity and quality of the antibody responses using label-free biosensing techniques.